2018
DOI: 10.22201/ib.20078706e.2018.0.2447
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad de la herpetofauna en la cuenca del Usumacinta, México

Abstract: Autor para correspondencia: amunoz_ecosur@icloud.com (L.A. Muñoz-Alonso) Recibido: 22 agosto 2017; aceptado: 10 septiembre 2018 ResumenSe presenta un estudio sobre la diversidad y riqueza de la herpetofauna de la cuenca del río Usumacinta, realizado a partir del análisis de 8,808 registros provenientes de colecciones científicas, de la base de datos faunística de la Comisión Nacional para el Conocimiento y Uso de la Biodiversidad, la revisión de referencias bibliográficas y de trabajo de campo, entre agosto de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The populations of D. mawii in the LRB were monitored in previous studies (Vogt and Flores-Villela 1992; Guichard-Romero 2006; Muñoz-Alonso et al 2018) and it was concluded that the main threats to their conservation were deforestation and the illegal extraction for trade. Recently the possible presence in the LRB of a lineage genetically different from other populations of D. mawii has been discussed (Martínez Gómez 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The populations of D. mawii in the LRB were monitored in previous studies (Vogt and Flores-Villela 1992; Guichard-Romero 2006; Muñoz-Alonso et al 2018) and it was concluded that the main threats to their conservation were deforestation and the illegal extraction for trade. Recently the possible presence in the LRB of a lineage genetically different from other populations of D. mawii has been discussed (Martínez Gómez 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The LRB has been identified as a priority area for conservation because of its high level of biological diversity (Ramírez et al 2022). Particularly, the LRB hosts a great diversity of herpetofauna, including some taxa that have not been described (Muñoz-Alonso et al 2018). However, this basin has continually been modified by changes in land use for livestock and agriculture (Vaca et al 2012(Vaca et al , 2019, affecting the wild populations of threatened species such as D. mawii (Legler and Vogt 2013;Muñoz-Alonso et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Sin embargo, estos números tienen altas posibilidades de elevarse, debido a las pocas exploraciones en las regiones remotas del Estado y por la amplia variedad de ecosistemas que se extienden desde las costas del Golfo de México, a lo largo de las llanuras de aluvión y hasta las elevaciones en los municipios de Huimanguillo, Teapa, Tacotalpa y Tenosique (Barragán-Vázquez, 2019;Guadarrama & Jiménez, 2019). En el Estado los estudios en la herpetofauna se han limitado a los listados señalados en las contribuciones de Smith (1944Smith ( , 1960 hasta los recientes por Barragán (2000Barragán ( , 2006; Barragán, Zenteno, Solis, López, Hernández, Martínez, Ríos, Hernández, Rodríguez, Peregrino, Rodríguez & González (2010), y Muñoz-Alonso, Rodiles-Hernández, López-León, González-Navarro, Chau-Cortés & Nieblas-Camacho (2018) Por lo anterior, los estudios de genética básica en la herpetofauna de Tabasco han sido poco abordados. En este documento, se hace una revisión profunda de los estudios de citogenética realizados en algunas especies nativas de la entidad, con énfasis en los hallazgos principales y de su aplicación para propósitos de conservación y para el desarrollo de modelos biológicos en el monitoreo ambiental de carácter pasivo.…”
Section: ----------------------------------------------------------unclassified